Identify the Learning Styles of St. Anthony Junior High School Students in the 2023/2024 Academic Year - Umbrella, Gabriel (Jurnal Ar Ro'is Mandalika (Armada), 2021)
Learning style is the way a person receives and processes information. Therefore, learning styles affect learning outcomes. Its significant influence raises understanding of learning styles, both as teachers and as learners is very necessary. This study is intended to describe the characteristics of the learning styles of students at SMP St. Antonius Padua Sentani. This study used accidental sampling method so that from 30 students who filled out the questionnaire there were 33% kinesthetic learners, 30% a uditory learners, and 27% visual learners. This figure shows that students of SMP St. Antonius Padua Sentani are active learners. They are more motivated to be directly involved in learning activities. Therefore, learning design at SMP S t. Antonius Padua Sentani needs to be more dominant in accommodating practicum and discussion activities to help kinesthetic and auditory learners. There is also a need to design more environments that feature diverse and engaging numeracy and literacy visuals to help visual learners.